(3TQM MOhO GdfMhs - (3YHO Gddg Hf CMeO Hf YHO Gddg Hf CMeO Hf Ydj GdaGcgj Gdecj, LeGd GdOjf,J (B972 (3g` s
(3ChdgG (B:s
(3CeG HYO, abO cfJ CdaJ MOhOkG aj GdfMh LeYJgG ef cJHg Ke SfM dj Cf CVY YdjgG TQMkG eeJRLkG HcdeGJgG s
(3BNQgG (B:s
(3hEPG Sei QLd H` jS cJH gcPG jS, hefge ef jcJHg jGSjf, hCNJGQ Hf GdMGLH, hGddg CYde HGdUhGH, ced s
(3HgG fXGe GdJYbjHIs
(3MOhO GdfMh ddTGQM CjVkGs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B28 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B472s
Keywords: (3GdfMhs